2013
DOI: 10.1007/978-3-642-40480-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Towards Many Gestures to One Command: A User Study for Tabletops

Abstract: Abstract. Multi-touch gestures are often thought by application designers for a one-to-one mapping between gestures and commands, which does not take into account the high variability of user gestures for actions in the physical world; it can also be a limitation that leads to very simplistic interaction choices. Our motivation is to make a step toward many-to-one mappings between user gestures and commands, by understanding user gestures variability for multi-touch systems; for doing so, we set up a user stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
(35 reference statements)
1
22
1
Order By: Relevance
“…Recognition of touch gestures has been done with algorithms specifically designed to discriminate between single-and multi-stroke gestures (Anthony and Wobbrock, 2010;Rekik et al, 2014;Vatavu, 2012;Vatavu et al, 2012;Wobbrock et al, 2007), and by employing multi-touch gesture toolkits Li, 2012, 2013). Researchers have also looked into users' gesture articulation patterns to understand more about their users and, consequently, improve the accuracy of existing recognition techniques (Anthony et al, 2013b;Rekik et al, 2013;Vatavu et al, 2013;Tu et al, 2012). For instance, Tu et al (2012) reported articulation differences between pen and finger stroke gestures.…”
Section: Understanding Touch and Designing Touch-screen Interactionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Recognition of touch gestures has been done with algorithms specifically designed to discriminate between single-and multi-stroke gestures (Anthony and Wobbrock, 2010;Rekik et al, 2014;Vatavu, 2012;Vatavu et al, 2012;Wobbrock et al, 2007), and by employing multi-touch gesture toolkits Li, 2012, 2013). Researchers have also looked into users' gesture articulation patterns to understand more about their users and, consequently, improve the accuracy of existing recognition techniques (Anthony et al, 2013b;Rekik et al, 2013;Vatavu et al, 2013;Tu et al, 2012). For instance, Tu et al (2012) reported articulation differences between pen and finger stroke gestures.…”
Section: Understanding Touch and Designing Touch-screen Interactionsmentioning
confidence: 96%
“…Also, touch input allows a multitude of possible outcomes for finger actions, ranging from simple taps, pinches, and swipes up to complex gestures with meaningful mappings to application functions (Hinrichs and Carpendale, 2011;Rekik et al, 2013;Wobbrock et al, 2009). Extra input modalities were also employed to accompany touch input and increase its expressibility, such as finger pressure (Heo and Lee, 2012;Hennecke et al, 2011) and sensing different parts of the finger anatomy (Harrison et al, 2011b).…”
Section: Understanding Touch and Designing Touch-screen Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the notion of gesture articulation difficulty has been mentioned as design criteria by many works [11,13,22], it has only been examined thoroughly for unistrokes [20]. However, opposed to unistrokes, multitouch gestures present considerably more degrees of freedom afforded during articulation, such as employing various number of fingers, different stroke count and ordering, and single-handed and bimanual input [15]. In this work, we examine users' perceived difficulty of multi-touch gesture articulation for symbolic gesture types [3,15,[19][20][21], such as those from Figure 1, and we provide the community the first understanding of this phenomenon as well as its potential implications in terms of gesture set design, multitouch recognizer development, and gesture-to-function mappings.…”
Section: Introductionmentioning
confidence: 99%
“…Designing gesture sets can prove a challenging task because of users' different preferences in terms of articulation patterns [2,15,16] and gesture-to-function mappings [22]. The current practice of gesture interface design has outlined several guidelines to assist Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Introductionmentioning
confidence: 99%